Serial Evaluation of Sequential Organ Failure Assessment Score in Predicting 1-Year Mortality in Critically Ill Patients - Md Ralib, Azrina; Said@Ahmad, Nor Azura; Ramly, Nur Fariza; Nanyan, Suhaila; Ismail, Mohd Nizamuddin; Mat Nor, Mohd Basri (IIUM Medical Journal Malaysia, 2022)
Introduction: Prediction of long-term prognosis or outcome in the intensive care unit (ICU) is important for prognostication and administration purposes. Sequential Organ Failure Assessment (SOFA) score was developed to estimate organ failure in sepsis patients. However, organ failures have been associated with mortality, and hence SOFA score has been validated as an outcome measure. To the best of our knowledge, the association of SOFA, and serial SOFA score with 1-year mortality was not well established. Materials and method: This was a retrospective observational cross sectional study using the existing record of patients admitted to general ICU Sultan Ahmad Shah Medical Centre from the 1st June 2017 to the 30thMay 2018. Data was collected from patients’ daily clinical charts and medical records. SOFA score on day-1 until day-3 and on discharge were recorded and subsequently delta SOFA was calculated. Results: A total of 120 patients’ data were collected. SOFA score within 3 days of admission predicted 1-year mortality, with the highest prediction for on SOFA score on discharge from ICU. Serial SOFA score measured within 24 hours (day 1 to day 2) and 48 hours (day 1 to day 3) did not predict mortality, but delta SOFA involving SOFA on discharged did. Cardiovascular and renal were the most significant individual component of SOFA score that contributed to 1-year mortality. Conclusions: SOFA score measured on discharge from ICU plays the key important factor in contributing to the prediction of 1-year mortality. Cardiovascular and renal were the most significant component that warrant risk stratification measures using the parameters.